Factors associated with awareness, knowledge and attitude towards prostate cancer among Malay men in traditional Malay villages, Negeri Sembilan, Malaysia - Ismail, Suriani; Zainuddin, Huda; Hamedon, Titi Rahmawati; Juni, Muhamad Hanafiah; Mohd Zulkefli, Nor Afiah; Muhamad Saliluddin, Suhainizam (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Background: Lack of awareness, poor knowledge and attitude regarding cancer have been identified as possible reasons accounting for the late presentation which lead to the poor survival of cancer patients in Malaysia. Method: A cross sectional study was conducted in three traditional Malay villages in Negeri Sembilan among adult males. Those who were already diagnosed with prostate cancer or Non Malaysians were excluded from the study. Data was collected using self-administered questionnaires which consist of several sections namely socio-demographic, awareness about prostate cancer, sources of information, family history of prostate cancer, lifestyle associated with risk of cancer, knowledge and attitude towards prostate cancer. Data was analysed using SPSS version 22.0. Chi-square test was used to determine associations. Level of significance was set at p<0.05. The knowledge and attitude scores were then categorized into 2 levels (50% or more of total score equals to ‘good’ and less than 50 % equals to ‘poor’). Results: A total of 168 respondents participated in this study and 62.1% of them had heard about prostate cancer and it is associated with level of education, monthly income and age (p= 0.023, 0.007 and 0.022). Most common sources of information are television, newspaper and friends (52.8%, 43.4% and 39.6% respectively). Among those who had heard about prostate cancer, 58.5% had good knowledge and this was significantly associated with smoking status (p=0.022). Conclusion: The percentage of awareness, knowledge and attitude regarding prostate cancer among the study population are still low. More effort should be carried out especially among men in rural communities to improve the situation.